Critical research advancements of flipped learning: a review of the top 100 highly cited papers. Issue 9 (3rd October 2022) - Cheng, Shu-Chen; Hwang, Gwo-Jen; Lai, Chiu-Lin
ABSTRACT: Highly cited articles have been revealed as being informative for research fields, topics, and trends. Through reading highly cited articles, researchers can gain fruitful results from previous studies and can identify essential clues and potential future research directions for their own research. Aiming at exploring the possibility of the application of and innovations in flipped learning, this study reviewed 100 highly cited articles related to flipped learning. By performing a literature review of the highly cited studies on flipped learning, we have discovered the proposed new learning strategies and flipped learning applied to the research topics that seldom draw attention, and the research fields that are less-frequently examined, including those research issues that are rarely discussed. We have also noticed that many studies have focused on comparing different flipped learning modes and identifying more effective flipped learning approaches. Only a minority of studies have compared the influences of flipped learning and traditional learning. Moreover, we found that researchers have tended to focus more on students' learning achievements and learning behaviors. Lastly, based on the reviews of the past flipped learning articles, this study provides suggestions from different perspectives. We hope to provide a reference for researchers and teachers to conduct flipped learning studies and design flipped learning activities in the future.